NATIONAL ANTHEM SINGING AT INTERNATIONAL SPORT COMPETITIONS: DOES THE DISCOURSE AGAINST KIMI GA YO AFFECT THE JAPANESE YOUTHS? - Shishido, Kumiko; Suarka, I Nyoman; Dhana, I Nyoman (E-Journal of Cultural Studies; Vol 16 No 2 (2023): Volume 16 Number 2 May 2023, 2023)
This paper aims to discuss the view of Japanese youths on the discourse against Kimi ga Yo , especially in the setting of international sport competitions. It is a qualitative-research that uses the open model survey technique to obtain the primary data from the Japanese youths aged 20 to 22. The result of this paper shows that the discourse against Kimi ga Yo does not implicate towards the youths’ view in the present days of Japan. It also highlights the youths’ ignorance on the literal meaning of the lyrics and their emphasis on the function of Kimi ga Yo as a national anthem. K e y words : Kimi ga Yo , critical discourse analysis, Japanese youths